KMH Cardiology and Diagnostic Centres selects Allstream to implement Managed Multiprotocol Label Switching service (Canada NewsWire, 2011)
This news release includes forward-looking statements and information (collectively, the "statements") about our corporate direction, business opportunities, operations, financial objectives, planned activities, future financial results and performance that are subject to risks, uncertainties and assumptions. As a consequence, actual results in the future may differ materially from any conclusion, forecast, anticipation or projection in such forward-looking statements. Examples of statements that constitute forward-looking information may be identified by words such as "believe", "expect", "project", "should", "anticipate", "could", "target", "forecast", "intend", "plan", "outlook", "see", "set", "pending", and other similar terms.